1997
DOI: 10.4141/p96-155
|View full text |Cite
|
Sign up to set email alerts
|

Performance of isolated microspore-derived doubled haploids of wheat (Triticum aestivum L.)

Abstract: . 1997. Performance of isolated microspore-derived doubled haploids of wheat (Triticum aestivum L.). Can. J. Plant Sci. 77: 549-554. Ploidy level, genetic stability and field performance of isolated microspore-derived wheat plants were evaluated. The ploidy levels of isolated microspore-derived wheat plants from cv. Chris and reciprocal crosses of Chris × Sinton were determined by two methods, namely chromosome counts of root tip cells and flow cytometric measurement of nuclear DNA content from leaves. Both me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Therefore, the similar magnitude of the variation of the DH lines from the two treatments, RT and MT, indicated that no mutations with a significant influence on the target fatty acids of the TE in the transgenic DH lines tested in this study had occurred during the in vitro culture process. This is consistent with studies on the genetic stability of DH progenies in cereals, in which about 90% of the DH lines were estimated to be genetically uniform (Hu and Kasha, 1997). These results support the use of MT for doubling the chromosome number since DH lines from MT and RT were shown to have a similar degree of homozygosity and MT is more convenient and more effective than RT (Mathias and Robbelen, 1991; Möllers et al, 1994).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the similar magnitude of the variation of the DH lines from the two treatments, RT and MT, indicated that no mutations with a significant influence on the target fatty acids of the TE in the transgenic DH lines tested in this study had occurred during the in vitro culture process. This is consistent with studies on the genetic stability of DH progenies in cereals, in which about 90% of the DH lines were estimated to be genetically uniform (Hu and Kasha, 1997). These results support the use of MT for doubling the chromosome number since DH lines from MT and RT were shown to have a similar degree of homozygosity and MT is more convenient and more effective than RT (Mathias and Robbelen, 1991; Möllers et al, 1994).…”
Section: Resultssupporting
confidence: 91%
“…In spite of that, all authors concluded that AC lines can be considered as an advantageous alternative to conventional breeding. The high genetic fidelity of wheat DH lines derived from isolated microspore culture and their performance similar to that of parent genotypes has been reported by Hu and Kasha (1997).…”
Section: Discussionsupporting
confidence: 57%
“…However, among all the plants that reached maturity, three that were identified as doubled haploid were partially sterile, and four plants classified as haploid produced single seeds. As pointed out by Hu and Kasha (1997), sterility might indicate aneuploidy that was not detected by flow cytometry because flow cytometry is incapable of distinguishing small differences in the nuclear content due to the absence of one small chromosome or its arm. The formation of single seeds in confirmed haploids might be due to localized chimerism for chromosome numbers or to the restitution of the first meiotic division.…”
Section: Discussionmentioning
confidence: 95%